Implementation of Public Relations Strategy Mix in Media Academy - Ari Budiarti; Ahmad Toni (LPPM Stikosa - AWS, 2022)
In the formation of an organization or company, from the beginning to its development, it is always inseparable from the ongoing process of interaction with various parties. Training institutions need a targeted and effective management strategy to compete with similar competitors. Media Academy is a training institution that is a new business unit in the Media Group corporate company utilizes the role of Public Relations to expand cooperation and establish relationships so that the company can be known more widely by the public. Public Relations Mix can be abbreviated as PENCILS, is one of the strategies of Public Relations related to the duties, roles, and functions depending on the path and the components possessed in this concept are related to the work carried out by Public Relations. This study aims to determine and analyze the implementation of the Public Relations Mix strategy at the Media Academy. The method used by researchers in this study is a qualitative descriptive approach. Data collection techniques in qualitative research are by conducting interviews, observations, and documentation studies. It can be concluded that the Public Relations strategy used by Media Academy has been successful because Media Academy has implemented seven PENCILS strategies as a Public Relations Mix strategy. It can be said that Public Relations is an integral part of the overall growth process of Media Academy as a new business unit in the Media Group corporate company.